Introduction to toxicology and food (CRC Press, 2003)
With growing interest in the safety of foods, knowledge of food toxicology is gaining more importance every day. Introduction to Toxicology and Food provides a concise overview of both the science of toxicology and food toxicology. It presents easy-to-understand explanations of the concepts and principles of toxicology as a science, the toxicants found in foods, and naturally occurring antitoxic/anticarcinogenic substances in foods. It examines the uses, harmful effects, and safety aspects of a variety of toxicants, including natural toxicants, contaminants, and food additives.